Respuesta :
Answer: -64
=======================================
Work Shown:
We have a geometric sequence
a = first term = -1
r = common ratio = (second term)/(first term) = 2/(-1) = -2
nth term
a(n) = a*(r)^(n-1)
a(n) = -1*(-2)^(n-1)
Now plug in n = 7 to get the 7th term
a(n) = -1*(-2)^(n-1)
a(7) = -1*(-2)^(7-1)
a(7) = -1*(-2)^6
a(7) = -1*(64)
a(7) = -64
The first seven terms are
-1, 2, -4, 8, -16, 32, -64
To get each new term, we multiply the last term by the common ratio -2
First, we need to find the rule for the sequence.
There’s not really an exact way to do this, you just have to look for a pattern.
This sequence follows the following notation:
An= -(-2^(n-1))
Then, we can plug 7 in for n.
A7 = -(-2^(n-1))
A7=-(-2^6)
A7=-64
There’s not really an exact way to do this, you just have to look for a pattern.
This sequence follows the following notation:
An= -(-2^(n-1))
Then, we can plug 7 in for n.
A7 = -(-2^(n-1))
A7=-(-2^6)
A7=-64